Development of a synthetic human thigh impact surrogate for sports personal protective equipment testing - Payne, T.; Mitchell, S.; Halkon, B.; Bibb, R.; Waters, M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2016)
Synthetic impact surrogates are widely used in the sporting goods industry in the evaluation of personal protective equipment. Existing surrogates, exemplified by those used in safety standards, have many shortcomings, primarily relating to their mass, stiffness, geometries and levels of constraint which limit their biofidelity and subsequent usefulness in personal protective equipment evaluations. In sports, absence from competition is a primary severity measure for injuries; consequently, blunt trauma injuries, such as contusions and lacerations, become pertinent and serious concerns. It is important, therefore, that synthetic surrogates provide an adequate description of these soft tissues to effectively evaluate injury risk. A novel, multi-material human thigh surrogate has been presented with consideration to the tissue structures, geometries and simulant materials used. This study presents the detailed development stages undertaken to fabricate a multi-material synthetic soft tissue surrogate with skin, subcutaneous adipose and muscle tissue components. The resultant surrogate demonstrates the successful use of sequential moulding techniques to construct a full-scale anatomical human impact surrogate which can be used in personal protective equipment testing.